(untitled) - Vardell, Sylvia M. (Westport, Conn., 2008)
Vardell provides an introduction to children and their literature through an activity-oriented survey of books that should be in your library. Written for librarians, the book offers practical applications to help you share books with children, as well as plans for book-based programs and ways to collaborate with teachers and families to share books with children. Each chapter includes brief insets of author comments, collaborative activities, featured books, special topics and activities, selected awards and celebrations, historical connections, recommended resources, issues for discussion, and assignment suggestions
Keywords: Children,Trẻ em; Books and reading,Sách và đọc sách